2017
DOI: 10.1039/c7sm01202k
|View full text |Cite
|
Sign up to set email alerts
|

Pinning susceptibility: a novel method to study growth of amorphous order in glass-forming liquids

Abstract: Existence and growth of amorphous order in supercooled liquids approaching glass transition is a subject of intense research. Even after decades of work, there is still no clear consensus on the molecular mechanisms that lead to a rapid slowing down of liquid dynamics approaching this putative transition. The existence of a correlation length associated with amorphous order has recently been postulated and also been estimated using multi-point correlation functions which cannot be calculated easily in experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…The arguments c and mimp have been suppressed in the following discussion, and their values have been held fixed at 12.5% and 4096, respectively. This can be related to the pinning susceptibility, χp(t), 20 via the following relation:…”
Section: Effect Of Heavy Impurities and The Effect Of Mass Heterogene...mentioning
confidence: 99%
“…The arguments c and mimp have been suppressed in the following discussion, and their values have been held fixed at 12.5% and 4096, respectively. This can be related to the pinning susceptibility, χp(t), 20 via the following relation:…”
Section: Effect Of Heavy Impurities and The Effect Of Mass Heterogene...mentioning
confidence: 99%
“…Using numerical simulation in Ref. [25], the validity of this relation has been checked, and it has also been shown that this scaling theory works if one uses large size particles having significantly lesser diffusion coefficients to act as 'soft pinning' sites. This finding makes this proposal very attractive to use in experiments, unlike hard pinning, as realizing soft pinning in a natural system will be much easier.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many existing methods to extract the desired static length scale, most of them are not useful for experiments on molecular glass-forming liquids. In a recent work [25], it has been shown that it is possible to extract static length-scale in a glass-forming liquid by measuring the response of the system in the presence of a small concentration of solute particles, which have a smaller diffusion constant than the constituent molecules or particles of the supercooled liquid medium. The idea mainly originated from the previous works on the effects of random pinning sites on the dynamics of the supercooled liquids [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations